KONSEP DIRI RESIDIVIS DI KOTA PEKANBARU - Perdana, Tegar Satria; Wirman, Welly (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Recidivist in fact socially ostracized by the community, this is because that recidivists do things that are contrary to religious values, ethics and morals. On the one hand should be placed as a social reality that is not inevitable existence.This study uses qualitative research with phenomenological approach. Subjects consisted of four convicts in the city of Pekanbaru selected by the snowball technique. The study used data collection techniques in-depth interviews, observation, and documentation study. To achieve the validity of the data in this study, researchers used the extension of participation and triangulation.The results showed that there are aspects of the self-concept consists of four aspects. The first aspect, which emphasizes the physiological aspects of physical elements, such as color, shape, weight or height, his countenance, had a healthy body condition, normal or disabled. The second aspect, which emphasizes the psychological aspects of cognition (intelligence, interest talent, creativity), affection (endurance, perseverance and tenacity to work, achievement motivation), and konasi (speed and accuracy of the work). The third aspect, Psycho-sociological aspects of the emphasis on understanding the individual who still has a relationship with the social environment that includes parents, siblings and relatives in the family. The fourth aspect, the aspect of Psycho-ethical and moral emphasis on an ability to understand and perform actions based on the values of ethics and morality.Keyword : The Concept Of Self, Recidivist , Crime, Jail.